Green and innovative supplier selection model via MCDM techniques and a case study in automotive industry - Büyükselçuk, Elif Çaloğlu (My University, 2017)
Yoğun rekabetin yaşandığı günümüz koşullarında, firmalar faaliyetlerini sürdürebilmek ve ayakta kalabilmek için bir takım önlemler almak zorundadırlar. Özellikle son yıllarda çevreye karşı olan hassasiyet artmış ve yenilikçi faaliyetler hız kazanmıştır. Bu da literatürde karşımıza iki yeni kavramı çıkarmaktadır: Yeşil ve Yenilikçi. Bu nedenle firmalar tedarik zincirlerini gözden geçirerek yeni bir tedarik zinciri yönetimi anlayışını benimsemektedirler. Başarılı bir tedarik zinciri yönetiminin birinci ve en önemli adımı da doğru tedarikçiler ile çalışmaktır. Ancak tedarikçi seçimi çok kriterli karar verme problemlerinden olup, çözümü karmaşık bir süreçtir. Bu çalışmada da, geleneksel tedarikçi seçim kriterlerinin yanı sıra yeşil ve yenilikçi tedarikçi seçimi kriterleri de göz önüne alınarak, otomotiv sektöründe faaliyet gösteren küçük ve orta ölçekli işletme (KOBİ) olan A firması için doğru tedarikçinin tespit edilmesi amacıyla bir model oluşturulmuştur. Tedarikçi seçim kriterlerinin ağırlıklarının belirlenmesinde AHP ve FAHP yaklaşımları kullanılmıştır. Kriterlerin ağırlıkları belirlendikten sonra doğru tedarikçinin belirlenebilmesi için literatürde sıkça karşımıza çıkan farklı çok kriterli karar verme (ÇKKV) teknikleri (örneğin; AHP, FAP, ANP, FANP, TOPSIS, FTOPSIS, VIKOR, FVIKOR ve GP) kullanılmıştır. Bu çalışmada DESTEC 1.0 ve DEMATSEL programları kullanılarak sonuçlar elde edilmiştir. Elde edilen sonuçlar karşılaştırılmış ve A firması için en uygun yeşil ve yenilikçi tedarikçi belirlenmiştir.

In today's environment that intense competition continues, companies must take some precautions in order to survive and be able to act their activities. Especially in recent years, sensitivity to the environment has been increased and innovative activities have accelerated. This reveals two new concepts in the literature: Green and Innovative. Therefore, companies are forced to adopt a new supply chain management by reviewing the existing supply chains. The first and most important step for a successful supply chain management is to collaborate with the right suppliers surely. However, supplier selection takes place into multiple-criteria decision making problem so solution of problem is a complex process. This study encourages that in addition to traditional criteria by taking into account green and innovative criteria, a model is constructed in order to identify the best supplier for company A that is a small and medium-sized enterprise (SME) operating in the automotive industry. AHP and FAHP approaches have been used to calculate the weight of the supplier selection criteria. After the determination of weight of criteria, different MCDM techniques that often encountered in the literature have been used (such as AHP, FAHP, ANP, FANP, TOPSIS, FTOPSIS, VIKOR, FVIKOR and GP) to identify the best supplier. The results were obtained by using DESTEC 1.0 and DEMATSEL solver. Obtained results have been compared and the best green and innovative (greenovative) supplier have been defined for company A.
Keywords: AHP; ANP; Bulanık Küme Teorisi; Çok Kriterli Karar Verme; Fuzzy Set Theory; Goal Programming; Hedef Programlama; Karar verme; Multi Criteria Decision Making; Otomotiv endüstrisi; Tedarik zinciri; TOPSIS; TOPSIS Supply Chain; Türkiye; VIKOR; Yönetim